Performance improvement capacity audit: A methodology for diagnosing capacity to improve irrigation performance - Merrey, Douglas J.; Murray-Rust, Hammond; Garcés-Restrepo, C.; Sakthivadivel, Ramaswamy; Wasantha Kumara, W.A.U. (1995)
This paper presents an objective easy-to-use methodology for rapidly assessing the capacity of the managers and users of an irrigation system to respond positively to interventions to improve performance, and for identifying the types of interventions likely to succeed. The 'Performance Improvement Capacity Audit' is based on five basic questions on the system design, operations, data collection, management framework and the will to manage. It is applied retrospectively on five systems to demonstrate its potential usefulness. The methodology complements others which focus on assessing actual and potential system performance.